2009
DOI: 10.4314/wiojms.v6i1.48229
|View full text |Cite
|
Sign up to set email alerts
|

The Dar es Salaam Seascape: A Case Study of an Environmental Management ‘Hotspot’

Abstract: Abstract-The Dar es Salaam seascape contains a variety of interacting coastal and marine ecosystems that support diverse resources, upon which human life has depended for centuries. This paper applies the UNEP Human-Environment Interaction Analytical Approach to examine the changes that have taken place in this seascape over the past few decades. The main drivers of change have been rapid population growth, poverty and inadequate education, together with global climate change. The main pressures have been dest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The Dar es Salaam city sewage dumps raw sewage into the shallow subtidal ocean through a pipe at Ocean Road beach that is located near the city centre (Wagner, 2007). From previous studies nutrient levels (nitrate, nitrite and phosphate), have been found to be significantly higher near this discharge point at Ocean road than in other sites studied (Hamisi et al, 2004).…”
Section: Study Areamentioning
confidence: 97%
“…The Dar es Salaam city sewage dumps raw sewage into the shallow subtidal ocean through a pipe at Ocean Road beach that is located near the city centre (Wagner, 2007). From previous studies nutrient levels (nitrate, nitrite and phosphate), have been found to be significantly higher near this discharge point at Ocean road than in other sites studied (Hamisi et al, 2004).…”
Section: Study Areamentioning
confidence: 97%
“…The creation of marine reserves can help the conservation of habitats (Samoilys et al 2015) and poverty alleviation (Wells et al 2007). Poverty has been identified as a cause of ecosystems degradation (Wagner 2008;UNEP-Nairobi Convention and WIOMSA 2015). However, a bottom-up approach integrating local communities is necessary for ecosystem-based management to be effective (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…These coastal areas are likely to see a faster and greater increase in population as people seek job opportunities and better living conditions (Neumann et al 2015). The combination of rapid population growth and poor planning of new coastal developments leads to important socioeconomic and environmental changes, often compromising the preservation of coastal ecosystems (Wagner 2008) and disproportionately affecting the most vulnerable people, who depend the most on ecosystem services (Samoilys et al 2015).…”
Section: Introductionmentioning
confidence: 99%